Glyptothorax maceriatus, a new species of sisorid catfish (Actinopterygii: Siluriformes) from north-eastern India - Ng, Heok Hee; _, Lalramliana (Zootaxa, 2012)
Glyptothorax maceriatus, new species, is described from the Meghna-Surma River system in Mizoram, northeast India.It differs from most congeners in the Indian subcontinent in having thoracic adhesive apparatus with a narrow elliptic cen-tral depression that is almost enclosed posteriorly by skin ridges. The following combination of characters serve to distin-guish it from congeners in the Indian subcontinent: nasal barbel not reaching anterior orbital margin; interorbital distance27.0–31.4% HL; head length 23.7–25.3% SL; head depth 12.5–14.2 % SL; thoracic adhesive apparatus with narrow el-liptic central depression that is almost enclosed posteriorly by skin ridges (striae) and with single, non-diverging series ofstriae running along its edges; width of adhesive apparatus 55.8–72.1% its length; unculiferous ridges of adhesive appa-ratus not extending anteriorly onto gular region; absence of striae on first pectoraland pelvic-fin elements; pectoral-finlength 20.7–24.9% SL; dorsal-spine length 13.0–17.1% SL; smooth posterior edge of dorsal spine; dorsal-to-adipose dis-tance 17.8–23.6% SL; body depth at anus 11.3–13.8% SL; pelvic-fin length 15.9–19.1 % SL; length of anal-fin base13.9–16.2% SL; caudal peduncle length 21.4–23.9% SL; and caudal peduncle depth 6.4–7.6% SL (3.1–3.4 times in its length).